(untitled) (Mustansiria Dental Journal, 2018)
Fifty four orthodontic patients wearing upper and lower fixed appliances were assigned either an electric tooth brush or a manual tooth brush. Each patient was instructed and trained on the proper use of the allocated brush. Clinical parameters included (Plaque index, Gingival index and Eastman interdental bleeding index) were measured at base line, at 4 weeks and at 8 weeks. Data for each group were analyzed using paired t-test. Patients using electric tooth brush and manual one showed a significant reduction in all clinical parameters at 4 and 8 weeks, but the reduction of the values of all parameters in electric brush group is higher than in manual group and the difference is statically significant. The present study concluded that electric tooth brush is real alternative to the often laborious manual tooth cleaning procedures used during active appliance therapy.